Benzoxazole-Directed Halogen Dance of Bromofuran - Miyagawa, Naoki; Murase, Yuki; Okano, Kentaro; Mori, Atsunori (Synlett, 2017)
A halogen dance of a benzoxazole-conjugated bromofuran derived from furfural is described. The reaction proceeds through a benzoxazole-directed lithiation to provide the α-lithiofuran, which is subjected to Negishi coupling to give α-arylated benzoxazole-conjugated furan derivatives. The synthetic utility of the reaction was demonstrated by transformation of the residual bromo group into a side chain bearing a siloxane moiety, which resulted in a significant improvement in solubility in organic solvents.
Keywords: halogen dance; one-pot reaction; cross-coupling; Negishi coupling; furan; oxazole